Characteristics of LC‐PUFA biosynthesis in marine herbivorous teleost Siganus canaliculatus under different ambient salinities. (21st October 2014) - Xie, D.; Wang, S.; You, C.; Chen, F.; Tocher, D.R.; Li, Y.
Abstract The present study aimed to characterize the influence of salinity on the biosynthesis of long‐chain polyunsaturated fatty acid (LC‐PUFA) in rabbitfish Siganus canaliculatus. An eight‐week feeding trial was performed in rabbitfish juveniles with diets containing fish oil (FO) or a blend of vegetable oils (perilla and Canola oils, VO) at two salinities, 32 and 10 ppt. The whole‐body fatty acid mass balance (FAMB) method was used to evaluate the in vivo LC‐PUFA biosynthetic activities, and the hepatic mRNA levels of Δ4 and Δ6/Δ5 fatty acyl desaturases (Fad) and elongase of very long‐chain fatty acids (Elovl5) genes were determined by real‐time quantitative PCR. The results showed that the ex novo production of LC‐PUFA in fish receiving the VO diet was significantly higher than fish fed the FO diet at both salinities. Furthermore, LC‐PUFA production at 10 ppt salinity was significantly higher than that at 32 ppt salinity in the VO dietary groups, whereas no effect of salinity was found in the FO dietary groups. Consistent with this, the calculated apparent in vivo desaturation and elongation activities were also higher in VO and low‐salinity treatments. In addition, higher levels of Δ4 and Δ6/Δ5 fads mRNA expression were obtained at low salinity, which was consistent with the calculated enzyme activities. In contrast, the expression of elovl5 was lower than that of fads, and the levels were not consistent with the elongase activity. The results suggest that ambient salinity may affect the activity of the LC‐PUFA biosynthetic pathway in rabbitfish through regulating fatty acyl desaturase and elongase activities, partly through a transcriptional control mechanism in the case of desaturases.